Composition of the essential oil of cistus laurifolius l. from Turkey - (:unkn) unknown (My University, 2004)
The water distilled essential oil of Cistus laurifolius L. from Turkey was analyzed by GC/MS. Sixty four compounds representing 67% of the oil were identified. Borneol (6.1%) and nonacosane (2.8%) were the major constituents. © 2004, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Cistus laurifoliusCistaceae; Essential oil composition